Uncommon plasmacytoid myoepithelioma originating from ectopic minor salivary gland in neck: a rare case with rare site presentation - Verma, Nidhi; Singh, Preeti; Saroj, Amod Kumar; Gupta, Priya (International Journal of Research in Medical Sciences, 2020)
The aim of this case report is to present as case of plasmacytoid at ectopic minor salivary gland in the neck which is a rare neoplasm with uncommon presentation of site. Usually it is a tumor of major salivary gland and more common in parotid gland and less common in the minor salivary gland of the oral cavity predominantly in palate. Here authors are discussing a case of 10-year-old female who presented in our institute with complain of swelling over right mid cervical region which was clinically suspected as reactive cervical lymph node. Patient was evaluated further and cytologically diagnosed as a case of plasmacytoid myoepithelioma. It was also confirmed as a case of plasmacytoid myoepithelioma after histopathology and immunohistochemistry studies. Plasmacytoid myoepithelioma at ectopic minor salivary gland site in the neck is uncommon presentation and only a limited number of cases have been reported in literature.